THE EFFECT OF FINANCIAL PERFORMANCE AND MACRO ECONOMIC FACTOR TO PROFITABILITY OF BIDDER COMPANIES - Linawati, Nanik; Halim, Richard (Jurnal Manajemen dan Kewirausahaan, 2017)
This study aims to determine the effects of leverage change, sales, market to book ratio; transaction cost, and interest rate after merger or acquisition on profitability change (return on assets or return on equity). The method used is multiple linear regressions. The type of data is cross sectional data. The samples are go public bidder companies that have annual or quarterly financial reports during one year before and after the merger or acquisition. The research results show leverage change, sales, market to book ratio, transaction cost and interest rate after merger or acquisition simultaneously have significant effect on the year and the next year change of return on asset or return on equity. Partially, leverage change and market to book ratio significantly influence on changes of profitability. Sales and interest rate significantly influence on the next year changes of profitability. Transaction cost partially has significant effect on next year changes of profitability.